Overview of rice quality in Panca Rijang District, Sidenreng Rappang Regency - Salfiana Salfiana (Program Studi Teknologi Hasil Pertanian Fakultas Sains dan Teknologi Hasil Pertanian Universitas Muhammadiyah Sidenreng Rappang, 2021)
Research is titled Overview of rice quality in Panca Rijang District, Sidenreng Rappang Regency. The research aims to measure or identify quantitatively the quality of rice in the District of Panca Rijang. Sampeling is obtained from a mobile car grinder, by taking a different sample from rice. The research was carried out by analyzing the water content of the sample, identification of head rice, broken grains, granular grains, red grains, yellow / damaged grains, calcifying grains, foreign objects and grain grains. The results showed that the five rice samples in Panca Rijang District, 80% met the requirements of the SNI 6128: 2015 quality class and 20% did not include the quality classes in accordance with the SNI SNI 6128: 2015. This shows that the quality of rice in Sidenreng Rappang Regency still needs to be improved, as well as maintaining the quality of rice that is in accordance with applicable quality standards.